Imam Ali (peace be upon him) and his theories of tax - Rida Sahib Abu Hamad (Iraqi Journal for Administrative Sciences, 2024)
I thank God and praise Him, and I pray and greet the Prophet Muhammad, his pure medical family, and his chosen companions. After all, the tax is one of the basic financial resources that the Islamic State relied on not only to finance its public expenses, such as carrying out Islamic conquests, providing protection from external attacks, and achieving internal security and justice, but also to achieve Many goals include establishing public ownership in addition to private ownership, and to support investment in the agricultural sector and other sectors, and to increase, produce, use, and reconstruct the country, as well as to improve the standards not only of the productive Kharaj class), but of all segments of society, because reforming the Kharaj people means reforming everyone else. This leads to the integrity and stability of the system. Through his sermons, books, letters, and wills, Imam Ali (the Most High) presented comprehensive theories and ideas about tax, which can be used in drawing up the correct financial policy in the country, with regard to tax, fees, taxes, and other aspects related to how to manage public property and care for the subjects, to achieve rates High in production and use, and hence in economic growth. The research hypotheses were determined by two hypotheses: The first is that Imam Ali (the Supreme) presented theories about tax, guaranteeing the right of the Islamic State to obtain a regular and fair financial resource from individual investors, in exchange for their investment in lands belonging to the state, and also guaranteeing the continued survival of these individual investors working in the sector. agricultural, and even motivates them to increase production and productivity levels to cover the amount of the tax. In other words, the theories presented by the Commander of the Faithful (peace be upon him) serve the tax, its people, and other social groups in society, and contribute to the reconstruction of the country and the integrity of the regime in it. As for the second hypothesis, it sees Imam Ali (the Most High) gave the standard specifications for each of the tax worker, the trustee, and the agent, and the tax money, and how to measure and deal with it.